Numerical simulation of KdV and mKdV equations with initial conditions by the variational iteration method - İnç, Mustafa (Pergamon-Elsevier Science Ltd, 2007)
A scheme is developed for the numerical study of the Korteweg-de Vries (KdV) and the modified Korteweg-de Vries (mKdV) equations with initial conditions by a variational approach. The exact and numerical solutions obtained by variational iteration method are compared with those obtained by Adomian decomposition method. The comparison shows that the obtained solutions are in excellent agreement. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: Nonlinear Differential-Equations; Approximate Solution; Principles; Burgers